2013
DOI: 10.2147/ceor.s44784
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the long-term effects of in vitro fertilization in Greece: an analysis based on a lifetime-investment model

Abstract: ObjectiveTo quantify the economic effects of a child conceived by in vitro fertilization (IVF) in terms of net tax revenue from the state’s perspective in Greece.MethodsBased on previous international experience, a mathematical model was developed to assess the lifetime productivity of a single individual and his/her lifetime transactions with governmental agencies. The model distinguished among three periods in the economic life cycle of an individual: (1) early life, when the government primarily contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
1
6
0
3
Order By: Relevance
“…The model’s time horizon is the individual’s life expectancy at birth in Spain in the base year (78 years), which is consistent with previously published empirical models ( Connolly et al, 2008 , Connolly et al, 2009 , Connolly et al, 2011 , Fragoulakis and Maniadakis, 2013 , Kröger and Ejzenberg, 2012 , Svensson et al, 2008 ). Table 2 lists the values assigned to the main parameters used in the base case scenario.…”
Section: Methodssupporting
confidence: 80%
See 2 more Smart Citations
“…The model’s time horizon is the individual’s life expectancy at birth in Spain in the base year (78 years), which is consistent with previously published empirical models ( Connolly et al, 2008 , Connolly et al, 2009 , Connolly et al, 2011 , Fragoulakis and Maniadakis, 2013 , Kröger and Ejzenberg, 2012 , Svensson et al, 2008 ). Table 2 lists the values assigned to the main parameters used in the base case scenario.…”
Section: Methodssupporting
confidence: 80%
“…It is also the first study to compare IVF with AI techniques. Previous studies that have calculated the NFC for the life cycle of an IVF-conceived individual have shown that this can vary, but that, with the exception of The Netherlands ( Moolenaar et al, 2014 ), it remains positive even in economic crisis scenarios: USD 61,428 in Brazil ( Kröger and Ejzenberg, 2012 ); GBP 109,939 in the UK ( Connolly et al, 2009 ); USD 155,870 in the USA ( Connolly et al, 2008 ); SEK 254,000 in Sweden ( Svensson et al, 2008 ); €154,100 in Denmark ( Connolly et al, 2011 ); and €60,435 in Greece ( Fragoulakis and Maniadakis, 2013 ). Our study indicates that public funding of assisted reproductive techniques is likely to result in a positive fiscal return for the Spanish Treasury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained in researches indicated that future monetary flows which would be produced by every human, particularly, tax revenues modified to current date (taking into account time value of money) will significantly exceed current and future expenses on procedures for birth and social support for a child till he (she) would achieve productive age. However, the result of estimation of net present value depends to a high degree on the level of labor productivity in a country, level of incomes, tax policy, and the state policy in the area of health care [9,10,11]. Carrying out of the above researches related to evaluation of long-term economic effects of more widespread use of in vitro fertilization allowed people making decisions in the health care area to obtain assessment of extent of economic burden bearing by the state in case of "unbirth" of every new child in a family suffering from infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Вице-премьер Ольга Голодец среди основных направлений стимулирования прироста населения, наряду с борьбой с абортами, мерами по снижению смертности, отметила применение вспомогательных репродуктивных технологий (ВРТ) [2]. Опыт многих стран показывает, что ВРТ как меры государственной политики по повышению рождаемости могут создать положительный доминирующий репродуктивный эффект [3,4]. С 1978 г. в мире более 7 млн младенцев рождены благодаря применению ВРТ, однако до сих пор во многих странах, в том числе в Российской Федерации, отсутствуют национальные регистры детей, что не позволяет в должной мере оценить их состояние здоровья.…”
unclassified